2019
DOI: 10.1620/tjem.249.213
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Exosomal miRNAs Derived from the Aqueous Humor of Myopia Patients

Abstract: Myopia is the most common refractive disorder in Eastern Asia. The development of myopia is associated with the cooperation of various ocular tissues. Exosomes in the aqueous humor (AH) have been implicated to modulate intracellular communications by transferring exosomal miRNAs and proteins between cells. These exosomal miRNAs and proteins are likely involved in the pathogenesis of various eye diseases. In this study, we aimed to explore human exosomal miRNA profiles and their roles in myopia development. AH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In the current study, we created a network including 28 miRNAs and 51 genes. Hsa-miR-17-5p, one of the miRNAs with the most gene interactions, was identified as a myopia-specific miRNA in a previous study ( Chen et al, 2019 ). Changes in the expression of miRNAs can influence a whole genetic network and alter the corresponding phenotype via PPIs.…”
Section: Discussionmentioning
confidence: 93%
“…In the current study, we created a network including 28 miRNAs and 51 genes. Hsa-miR-17-5p, one of the miRNAs with the most gene interactions, was identified as a myopia-specific miRNA in a previous study ( Chen et al, 2019 ). Changes in the expression of miRNAs can influence a whole genetic network and alter the corresponding phenotype via PPIs.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have shown that miRNA, as a biomarker of DME, has high sensitivity and specificity (11) and is stably expressed in biological fluids such as human AH and plasma (34,35). Among them, overexpression of miR-155-5p has been proved by numerous studies to play an important role in the progression of diabetes (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, trabecular meshwork cells released exosomes containing myocilin under the stimulation of the external environment [26,27]. Different expression profiles of exosomal miRNAs were found to be associated with glaucoma and myopia [28,29]. To analyze the alteration of exosomal proteins that occur with myopia, we aimed to compare the individual protein profile from nine high myopia patients with nine control patients by using liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Ivyspringmentioning
confidence: 99%